Effects of glycerol in tris extender on frozen semen quality of crossbred Etawah bucks - Surya Natal Tambing; Mozes R Toelihere; Tuty L Yusuf; I ketut Sutama (Indonesian Center for Animal Research and Development (ICARD), 2000)
Bucks semen is easily damaged during freezing process, due to the formation of ice crystals. Consequently, semen quality decreases particularly the post-thaw sperm motility, viability, intack plasma membrane and intack acrosomal cap. The objectives of this research are to determine the optimum dose of glycerol in Tris extender in maintaining frozen semen quality of crossbred Etawah bucks. Four head of PE buck of 2 - 4 years old were used in this experiment. Doses of glycerol used were 5%, 6% and 7%. Semen was collected once a week using artificial vagina. Results of this experiment indicated that the mean percentage of pre-freezing motility, live sperm, sperm with intact plasma membrane and intact acrosomal cap in 5%, 6% and 7% glycerol were not significantly different (P>0.05). After freezing, the mean percentage of motility, live sperm, sperm with intact plasma membrane and intact acrosomal cap in 6% glycerol (52.60%, 65.03%, 45.63% and 47.54% respectively) were significantly higher (P<0.05) than in 5% (44.31%, 52.00%, 37.60% and 37.00% respectively) and in 7% glycerol (45.28%, 52.10%, 37.97% and 37.14% respectively). However, there were not significant differences in 5% and 7% glycerol for any parameter measured. It was concluded that supplementation of glycerol 6% in Tris extender effective to protect of sperm from various shock during the process of semen cryopreservation, so that it could maintain of frozen semen quality (sperm motility, viability, intack plasma membrane and intack acrosomal cap) that suitable used in AI program of crossbred Etawah bucks. Key words : Glycerol, PE bucks, semen quality